Alpha-Lipoic Acid as a Nutritive Supplement for Humans and Animals: An Overview of Its Use in Dog Food - Reshma M. Anthony; Jennifer M. MacLeay; Kathy L. Gross (Animals, 2021)
Alpha-lipoic acid (a-LA) is used as a nutritive additive in dog food. Therefore, we performed a systematic review of studies published to date in PubMed, Google Scholar, Cochrane Library and MedlinePlus involving alpha-lipoic acid supplementation, which included human clinical trials as well as animal studies, to evaluate its utility as a supplement in foods for healthy, adult dogs. While an upper limit of alpha-lipoic acid intake in humans has not been conclusively determined, the levels for oral intake of a-LA have been better defined in animals, and distinct differences based on species have been described. The maximum tolerated oral dose of a-LA in dogs has been reported as 126 mg/kg body weight and the LD50 as 400 to 500 mg/kg body weight. The antioxidant, anti-inflammatory and neuro-protective benefits of alpha-lipoic acid in dogs were observed at concentrations much lower than the maximum tolerated dose or proposed LD50. At concentrations of 2.7–4.94 mg/kg body weight/day, alpha-lipoic acid is well tolerated and posed no health risks to dogs while providing improved antioxidant capacity. This review thereby supports the utility of alpha-lipoic acid as an effective nutritive additive in dog food.